2018
DOI: 10.1155/2018/3095961
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Treatment with Dexamethasone Intravitreal Implant in Cystoid Macular Edema Secondary to Retinal Vein Occlusion

Abstract: Purpose To evaluate retinal functional improvement by means of visual acuity and retinal sensibility examination after intravitreal dexamethasone implant in patients affected by cystoid macular edema secondary to retinal vein occlusion. Methods Twenty-six consecutive patients affected by retinal vein occlusion complicated by cystoid macular edema were enrolled in this prospective interventional study. All patients underwent a baseline complete ophthalmological evaluation as well as retinal angiography, OCT exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It is used to treat macular edema secondary to RVO as well as diabetic retinopathy, noninfectious uveitis, and pseudophakic cystoid macular edema (PCME; Irvine–Gass syndrome). 810…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat macular edema secondary to RVO as well as diabetic retinopathy, noninfectious uveitis, and pseudophakic cystoid macular edema (PCME; Irvine–Gass syndrome). 810…”
Section: Introductionmentioning
confidence: 99%
“…Also, some studies whose final outcome was not BCVA and CRT, the results were not reported, and patients had already received other treatments were also excluded. Finally, seven eligible studies including 393 eyes were used in the present meta-analysis [7][8][9][10][11][12]. The flow chart for the study selection process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Administration of IVDI has been reported to improve retinal sensitivity in the central 10°in both eyes in cases of CME secondary to diabetes or central vein occlusion. 24,25 Topical CAI has also been shown to be effective in improving central retinal sensitivity in patients with RP. 15,19 Here we tested whether there could be changes in retinal sensitivity in the central 5°a nd 10°in eyes with RP-related CME undergoing IV-DI.…”
Section: Discussionmentioning
confidence: 99%